PENGENALAN Pengenalan Pembuktian Matematika untuk Siswa: Membangun Dasar Logika dan Pemahaman - Selpi Saputri; Annisatul Mardiah Nasution; Oka Diana Sabilla.S; Dina Mardiana; Nadia Authari; Sonia Sonia; Muhammad Win Afgani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the role and strategies of introducing mathematical proofs appropriately for students, as well as to describe their contribution to enhancing logical, critical thinking, and understanding of mathematical concepts. The method used is library research with a descriptive qualitative approach through the analysis of various current scientific literature relevant to mathematics learning and education. The results of the study indicate that mathematical proofs not only function as a tool for verifying the truth of a statement but also as an epistemological process that develops deductive, argumentative, and reflective reasoning skills in understanding the structure and relationships of mathematical logic. Effective introduction strategies include the use of visual representations, collaborative learning, linguistic scaffolding, and the application of a gradual approach from informal argumentation to formal deduction. The approach has been proven to enhance students conceptual understanding, argumentative skills, and logical awareness. The implication is that proofs need to be systematically integrated into mathematics learning in secondary schools to strengthen Higher Order Thinking Skills (HOTS) and develop a scientific mindset in accordance with the principles of the Merdeka Curriculum